Kinetics of Inversion of Dichlorobutene in the Heterogeneous System - Samadani Langeroodi, N. (Asian Journal of Chemistry, 2012)
The reaction kinetics of the isomerization of 3,4-dichlorobutene-1 to 1,4-dichlorobutene-2 was investigated by using gas-liquid chromatography in presence of Fe2O3/ZrO2 as solid catalyst. At the optimizing conditions, the catalytic activity, rate constants of reaction and activation energy have been evaluated using kinetic equations. The structure of the catalyst was investigated by using Mossbauer spectroscopy.